2020
DOI: 10.3390/horticulturae6040075
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Hardy Grape Cultivar Winter Injury and Trunk Re-Establishment Following Severe Weather Events in North Dakota

Abstract: Extreme winter temperatures during the 2018–2019 dormant season contributed to trunk collapse and complete trunk death of numerous genotypes throughout a diverse grapevine planting in eastern North Dakota, USA. Through the early portion of the dormant season, 12 genotypes were screened to identify lethal temperature exotherms of primary buds; from these results, none were anticipated to be fully prepared to survive the −37 °C minimum temperature recorded in the region. Trunk collapse, death, and survival were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In either case of winter injury often the roots and the lower trunk of vines are protected by the insulating snow covering. Thus, trunk replacement by sucker is a viable and common management strategy in the NMW [ 84 ]. Regardless, associated observations of winter injury, vascular discoloration, and identification of fungi suggests our second hypothesis is true and that the polar vortex likely predisposed grapevines to these opportunistic canker pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In either case of winter injury often the roots and the lower trunk of vines are protected by the insulating snow covering. Thus, trunk replacement by sucker is a viable and common management strategy in the NMW [ 84 ]. Regardless, associated observations of winter injury, vascular discoloration, and identification of fungi suggests our second hypothesis is true and that the polar vortex likely predisposed grapevines to these opportunistic canker pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the maximum freezing tolerance occurs in January and then begins to decrease with increasing temperatures in February or March [31][32][33]. Interspecific cultivars are reported to have a wide range of inherent cold hardiness and winter survival characteristics [2,33]. The results of this study showed the complex interactions of the grapevine cultivar freezing tolerance and bud dormancy phenotype in response to changing temperatures.…”
Section: Discussionmentioning
confidence: 89%
“…Freezing injury is one of the most problematic issue impacting production of grapevine in Northern regions of the United States [1][2][3]. The freezing tolerance of grapevine species and cultivars varies considerably with Vitis riparia having the greatest reported tolerance of −40 • C [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, grapevine is the leading horticultural crop in terms of production quantity (FAO, 2020). Freezing injury is one of the major issues restricting grapevine production in many northern regions of the United States [1][2][3].…”
Section: Introductionmentioning
confidence: 99%